2010
DOI: 10.2147/ceor.s5101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic considerations of antiobesity treatment: a review of orlistat

Abstract: The objective of this study was to review the current knowledge about the use of orlistat from clinical and economic perspectives, and to assess this drug’s public health impact. Weight reduction by current antiobesity drugs, compared to placebo, is at most around 5 kg. Orlistat, the most studied antiobesity drug, is associated with the least-severe adverse effects, but compared with other drugs in its class it also delivers the most modest weight loss versus placebo (less than 3 kg). Orlistat appears to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 106 publications
0
9
0
1
Order By: Relevance
“…The multiple benefits observed are in contrast to treatments such as pharmacological interventions, approaches that are usually intended to treat one outcome. In addition, orlistat, the only pharmacological intervention currently approved in the United States for the treatment of obesity in children and adolescents [ 93 ], has been shown to be less cost-effective than several nonpharmacologic interventions, including exercise [ 87 , 94 ], and has also been accompanied by side-effects such as gastrointestinal distress [ 95 ]. With respect to exercise in the current meta-analysis, four studies that did include information on side-effects reported no serious adverse events [ 74 , 77 79 ], defined as any intervention that results in death, a life threatening condition, hospitalization (initial or prolonged), disability, or permanent damage [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…The multiple benefits observed are in contrast to treatments such as pharmacological interventions, approaches that are usually intended to treat one outcome. In addition, orlistat, the only pharmacological intervention currently approved in the United States for the treatment of obesity in children and adolescents [ 93 ], has been shown to be less cost-effective than several nonpharmacologic interventions, including exercise [ 87 , 94 ], and has also been accompanied by side-effects such as gastrointestinal distress [ 95 ]. With respect to exercise in the current meta-analysis, four studies that did include information on side-effects reported no serious adverse events [ 74 , 77 79 ], defined as any intervention that results in death, a life threatening condition, hospitalization (initial or prolonged), disability, or permanent damage [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…When imputing missing data only, the underlying assumption is that body weight would be unaffected by discontinuation for trial participants lost to follow up. Participants typically experience weight regain after discontinuing an effective treatment [ 33 ]; therefore, the assumption of no weight change post-discontinuation required by this version of the LOCF approach is unrealistic.…”
Section: Estimating Treatment Effects: Accounting For Intercurrent Events and Handling Missing Datamentioning
confidence: 99%
“…For the large number of patients who are not able to reduce weight by non‐pharmacological means, drug treatment offers a reasonable option to treat obesity . Orlistat (tetrahydrolipstatin) is a lipase inhibitor that blocks around one‐third of intestinal fat digestion . It is currently the only drug approved by both the European Medical Agency (EMA) and the US Food and Drug Administration (FDA) for the long‐term treatment of obesity.…”
Section: Introductionmentioning
confidence: 99%